Targeting Myadm to Intervene Pulmonary Hypertension on Rats Before Pregnancy Alleviates the Effect on Their Offspring’s Cardiac-Cerebral Systems - Wang, Jingrong; Zhang, Zirui; Liang, Cui; Lv, Tingting; Yu, Haoying; Ren, Shuyue; Lin, Peirong; Du, Guanhua; Sun, Lan (Frontiers in Pharmacology, 2022)
Pregnancy with pulmonary hypertension (PH) seriously threatens the life and safety of mothers and infants. Here, we focused on the long-term effect of maternal PH on postpartum growth of rat offspring for the first time, as well as explored the role of Myadm in female PH rats before pregnancy based upon our previous findings. Patients with PH are prone to hypoxemia, leading to insufficient placental structure and function, which affects the organ function of fetuses, followed by evidence that differently expressed genes (DEGs) existed in the heart of maternal PH newborn rats and enriched in pathways related to cardiac and nerve development on human infants with similar birth outcome-low birth weight (LBW). LBW was one of the possible birth outcomes of pregnancy with PH, especially severe PH, accompanied by evidence that offspring derived from mothers with PH presented lower birth weights and slower growth rats than those derived from normal control mothers in a rat model. Besides, maternal PH rat offspring showed cardiac remodeling and a significant elevation of the expression levels of hypoxia- and inflammation- related markers in the cerebral cortex at both ten and fourteen weeks of age, respectively. What’s more, our previous studies found that the overexpression of Myadm could result in the remodeling of pulmonary artery. And targeting Myadm to intervene PH before pregnancy could alleviate sustained low weight growth in maternal PH rat offspring, as well as the pathological changes of cardiac-cerebral system caused by maternal PH, including enlarged right heart cavity, loss of cardiomyocyte, abnormal heart index and cerebral cortex hypoxia and inflammatory state as they grew up, to a certain extent. Our findings show the pathological significance of maternal PH on offspring growth and cardiac-cerebral development in a rat model, as well as point out the potential treatment target, which may provide a further reference for pregnancy outcomes in women with PH and healthy development of offspring to some extent.